EFEKTIVITAS LAYANAN HUMAS KEMENTERIAN KOPERASI DAN UKM RI #PASARSENENUKM DI MEDIA SOSIAL INSTAGRAM @KEMENKOPUKM TERHADAP PENINGKATAN PROMOSI UKM DI INDONESIA (Survey Terhadap followers Instagram @KemenkopUKM) - Alysha Tri Wardhani (2020)
The effectiveness of public relations services from the Ministry of Cooperatives and SMES #pasarsenenUKM on social media Instagram @KemenkopUKM to increase promotion of SMES in Indonesia (Survey of Instagram followers @KemenkopUKM Alysha Tri Wardhani ABSTRACT This Research is intended to measure the effectivity of The Public Relation service of The Ministry of Cooperation and Small and Medium Business (SMB) #pasarsenenUKM on Instagram social Media towards the enhancement of SMB prospect (Surveys of Instagram follower of @KemenkopUKM account). The relevant concept and theory of this research is The Hierarchy of Effects Concept. This research uses a quantitative approach, with a survey method using a questionnaire. The sample in this study is followers of Instagram @KemenkopUKM with 100 respondents. The sampling technique in this study uses non probability sampling with the type of purposive sampling which means the method for determining the sample is done by determining the target of the population element. The data testing technique using the Windows Statistics Program for Social Science (SPSS) version 22. The result of this study indicate that the correlation between variable X (Effectiveness of Public Relations Services) with Y variable (Promotion of SMEs) has a strong relationship of 0.769. Based on the calculation of the coefficient of determination results obtained the influence of variable X on variable Y by 59%. The results of the hypothesis test with a t count of 11,912 which can be concluded that Ho is rejected and Ha is accepted, which means there is a significant influence between the effectiveness of the Ministry of Cooperatives and SMEs #pasarsenenUKM public relations services on Instagram @KemenkopUKM social media on increasing promotion of SMEs in Indonesia. Keywords : Instagram, Ministry of Cooperation and Small and Medium Busines, Service Effectivity, SMB Promotion